Isolasi dan Karakterisasi Selulase dari Trichoderma Viride dan Rhizopus Spp dengan Substrat Jerami Padi - Montesqrit Montesqrit (Universitas Andalas, 2007)
The objectives of this study were to isolated and produce cellulase from soil molds and to characterize the enzyme. The strains of mold isolated from soil, namely Rhizopus spp and one cultured mold. Trichoderma viride, was used to produce the enzymes. Medium for enzyme production consisted of NH4NO3, KCl, FeSO4.7H2O, MgSO4.7H2O, CuSO4.2H2O and rice straw as a sole source of carbon (pH : 5.45). Culture was done at 28oC for 5,8,11 and 14 days with shaking at 150 rpm. Using this method cellulase production was optimum at 14 days with substrat concentration of 1.5% for T. viride culture. However the optimum production of cellulase for Rhizopus spp culture were three days shorter than culture of T.viride with substrat concentration of 1.5 and 1% respectively. Temperature and pH optimal activity of cellulases were as follow : cellulase from T.viride at temperature 60oC and pH 5 and cellulase from Rhizopus spp at temperature 50oC and pH 5. While temperature and pH stability of cellulases were as follow : cellulase from T. viride at temperature 30 - 80oC and pH 3 - 7 and cellulase from Rhizopus spp at temperature 30 - 80oC and pH 3-6. It was concluded that molds can grow on rice straw as a sole source of carbon produce cellulases.